2016
DOI: 10.2807/1560-7917.es.2016.21.48.30413
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus cereus-induced food-borne outbreaks in France, 2007 to 2014: epidemiology and genetic characterisation

Abstract: The aim of this study was to identify and characterise Bacillus cereus from a unique national collection of 564 strains associated with 140 strong-evidence food-borne outbreaks (FBOs) occurring in France during 2007 to 2014. Starchy food and vegetables were the most frequent food vehicles identified; 747 of 911 human cases occurred in institutional catering contexts. Incubation period was significantly shorter for emetic strains compared with diarrhoeal strains A sub-panel of 149 strains strictly associated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 29 publications
6
95
1
1
Order By: Relevance
“…thuringiensis ) and VII ( B. cytotoxicus ) may have the ability to cause foodborne illness. This is consistent with a recent study that reported that strains from multiple B. cereus group clades have been previously implicated as the causative agent in foodborne outbreaks ( 66 ). Among the isolates characterized here, all clade VI isolates were capable of growing at 6°C, but none of these isolates were cytotoxic in tissue culture when grown at 37°C.…”
Section: Discussionsupporting
confidence: 93%
“…thuringiensis ) and VII ( B. cytotoxicus ) may have the ability to cause foodborne illness. This is consistent with a recent study that reported that strains from multiple B. cereus group clades have been previously implicated as the causative agent in foodborne outbreaks ( 66 ). Among the isolates characterized here, all clade VI isolates were capable of growing at 6°C, but none of these isolates were cytotoxic in tissue culture when grown at 37°C.…”
Section: Discussionsupporting
confidence: 93%
“…The most common enterotoxin-encoding genes in the B. cereus strains we identified were the nhe and entFM, consistent with previous reports (Kim et al, 2010;Chon et al, 2015;Hwang and Park, 2015;Glasset et al, 2016;Gao et al, 2018;Yu et al, 2019). CytK is a cytotoxin isolated from a B. cereus strain that caused a severe food poisoning outbreak leading to three deaths in France (Lund et al, 2000).…”
Section: Virulence Gene Profiles Of B Cereus Isolatessupporting
confidence: 90%
“…B. cereus can cause food poisoning even at very low doses, with more than 10 3 B. cereus g −1 considered unsafe for consumption (Granum and Lund, 1997). Despite safety precautions, numerous food poisoning incidents caused by B. cereus have been reported recently in Spain (Doménech-Sánchez et al, 2011), Belgium (Delbrassinne et al, 2015), Argentina (Lopez et al, 2015), Australia (Sloan-Gardner et al, 2014), England (Nicholls et al, 2016), Austria (Schmid et al, 2016), and France (Glasset et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…B. weihenstephanensis, some strains have been identified as pathogens for humans (Ceuppens et al, 2013;. Among these, B. cereus has been identified in a large diversity of foods (dairy products, fresh vegetables and others), causing important worldwide epidemiological crises, and in some cases, even death by emetic and diarrheal infections (Oh et al, 2012;Glasset et al, 2016). Also, B. thuringiensis strains have recently been related to intoxications caused by the ingestion of contaminated foods (Oh et al, 2012).…”
Section: Discussion and Perspectives Of Biosecurity And Biodiversity mentioning
confidence: 99%
“…Entre éstos, B. cereus se ha identificado en una gran diversidad de alimentos (productos lácticos, vegetales frescos, entre otros), provocando crisis epidemiológicas importantes a nivel mundial, y en algunos casos hasta la muerte, debido a infecciones eméticas y diarreicas (Oh et al, 2012;Glasset et al, 2016). Además, recientemente, cepas de B. thuringiensis han sido asociados a intoxicaciones por el consumo de alimentos contaminados (Oh et al, 2012).…”
Section: Discusión Y Perspectivas De Bioseguridad Y Biodiversidad En unclassified